Protection mechanism and deployment cost analysis for Ethernet PON FTTH access network - P'ng, Won Tiang; Shaari, Sahbudin; Khatun, Sabira; Abdullah, Mohamad Khazani (IEEE, 2006)
In this paper, a new protection method for access network is proposed where redundant equipments are not required and protection is provided to end user through sharing of available timeslots during the failure time.